2022
DOI: 10.1002/ptr.7450
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 ameliorates mitochondrial dysfunction to circumvent neuronal energy failure in acute phase of focal cerebral ischemia

Abstract: Due to sudden loss of cerebral blood circulation, acute ischemic stroke (IS) causes neuronal energy attenuation or even exhaustion by mitochondrial dysfunction resulting in aggravation of neurological injury. In this study, we investigated if Notoginsenoside R1 ameliorated cerebral energy metabolism by limiting neuronal mitochondrial dysfunction in acute IS. Male Sprague–Dawley rats (260–280 g) were selected and performed by permanent middle cerebral artery occlusion model. In vitro, the oxygen glucose depriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…NGR1 has expressed capabilities such as antioxidant generation (Li et al, 2021; Luo et al, 2022; Zhao et al, 2020), apoptosis inhibition (Liu et al, 2021; Zhu et al, 2020), autophagy attenuation (Cao et al, 2021), mitochondrial function protection (Liu et al, 2021, 2022; Wang, Tang, et al, 2021; Wang, Wu, et al, 2021), and lipid metabolism regulation (Lei et al, 2022; Tian et al, 2022). However, its effect on early porcine embryos has so far remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGR1 has expressed capabilities such as antioxidant generation (Li et al, 2021; Luo et al, 2022; Zhao et al, 2020), apoptosis inhibition (Liu et al, 2021; Zhu et al, 2020), autophagy attenuation (Cao et al, 2021), mitochondrial function protection (Liu et al, 2021, 2022; Wang, Tang, et al, 2021; Wang, Wu, et al, 2021), and lipid metabolism regulation (Lei et al, 2022; Tian et al, 2022). However, its effect on early porcine embryos has so far remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional Panax ginseng medicinal extract, NGR1 is recognized and commonly used in Chinese herbal medicine. Several studies have observed that specific NGR1 doses can enhance early embryonic development by protecting mitochondria function and thereby reducing oxidative stress (Liu et al, 2022; Luo et al, 2022; Meng et al, 2014; Sun et al, 2013). However, NGR1's effect on preimplantation porcine embryonic development has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, these mitochondrial abnormalities were prevented by piperine pretreatment ( Kaushik et al, 2021 ). In vitro , OGD/R induced mitochondrial fragmentation, mitochondrial enlargement, mitochondrial number reduction, and mitochondrial swelling, which could be alleviated by pretreatment with notoginsenoside R1 ( Zhu et al, 2021 ; Liu et al, 2022 ), hydroxysafflor yellow A ( Huang et al, 2021 ), and calenduloside E ( Li et al, 2022b ). Ginsenoside Rd and piperine pretreatment improved mitochondrial energy metabolism after cerebral I/R injury ( Ye et al, 2011 ; Kaushik et al, 2021 ) whereas notoginsenoside R1 and notoginseng leaf triterpene pretreatment improved mitochondrial energy metabolism after OGD/R injury ( Xie et al, 2020 ; Zhu et al, 2021 ; Liu et al, 2022 ).…”
Section: Progress In Ischemic Stroke Prevention and Treatment Using T...mentioning
confidence: 99%
“…In vitro , OGD/R induced mitochondrial fragmentation, mitochondrial enlargement, mitochondrial number reduction, and mitochondrial swelling, which could be alleviated by pretreatment with notoginsenoside R1 ( Zhu et al, 2021 ; Liu et al, 2022 ), hydroxysafflor yellow A ( Huang et al, 2021 ), and calenduloside E ( Li et al, 2022b ). Ginsenoside Rd and piperine pretreatment improved mitochondrial energy metabolism after cerebral I/R injury ( Ye et al, 2011 ; Kaushik et al, 2021 ) whereas notoginsenoside R1 and notoginseng leaf triterpene pretreatment improved mitochondrial energy metabolism after OGD/R injury ( Xie et al, 2020 ; Zhu et al, 2021 ; Liu et al, 2022 ). In vivo ( Ye et al, 2011 ; Mukherjee et al, 2019 ; Zhang et al, 2019 ; Huang et al, 2021 ; Kaushik et al, 2021 ) and in vitro ( Li et al, 2017 ; Wu et al, 2017 ; Zhou et al, 2017 ; Huang et al, 2020 ; Xie et al, 2020 ; Li et al, 2021 ; Huang et al, 2021 ; Li et al, 2022b ; Ni et al, 2022 ; Peng et al, 2022 ) studies have reported that TCM compounds (e.g., piperine, ginsenoside Rd, hydroxysafflor yellow A, β-patchoulene, curcumin, ginsenoside Rb1, artemether, notoginseng leaf triterpenes, ginkgolide k, ginsenoside monomer compound k, tanshinone IIA, artemisinin, and kaempferol) inhibited oxidative stress and mPTP and upregulated MMP levels.…”
Section: Progress In Ischemic Stroke Prevention and Treatment Using T...mentioning
confidence: 99%
See 1 more Smart Citation